New PID Controller Design for Multi-Switching Hyperchaotic Synchronization with Real-World Application - Hammami, Sonia (Journal of Applied Nonlinear Dynamics, 2026)
This paper is devoted to design discrete PID controller for hyperchaos multi-switching synchronization. The dominant pole placement problem with such discrete PID controllers in z-domain is studied since it is important to take advantage of discrete domain representation, especially, during the pole placement procedure. Moreover, it is shown that modified Nyquist plot method is still valid in discrete domain and it is possible to find relevant discrete PID controller parameters. Then, the feasibility as well as the performance of the proposed approach of multi-switching combination synchronization, based on PID controller, is checked through its practical application in information transmission field to ensure more security of the message signal by means of hyperchaotic masking. Finally, experimental simulations are carried out in order to assess the security analysis and demonstrate that the suggested cryptosystem is large enough to resist to the noise attack thanks to its excellent encryption robustness.